2017
DOI: 10.1038/cgt.2017.16
|View full text |Cite
|
Sign up to set email alerts
|

New methods in the diagnosis of cancer and gene therapy of cancer based on nanoparticles

Abstract: Cancer is one of the leading cause of death in the world with the prevalence of >10 million mortalities annually. Current cancer treatments include surgical intervention, radiation, and taking chemotherapeutic drugs, which often kill the healthy cells and result in toxicity in patients. Therefore, researchers are looking for ways to be able to eliminate just cancerous cells. Intra-tumor heterogeneity of cancerous cells is the main obstacle on the way of an effective cancer treatment. However, better comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
129
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(133 citation statements)
references
References 104 publications
0
129
0
4
Order By: Relevance
“…With regard to clinical science, the potential applications of nanotechnology are huge, and has already generated a range of promising examples, such as conceptually new medical diagnostics, imaging agents and therapeutics (using new drug-delivery platforms) for detecting and treating diseases [18,[26][27][28][29] in the early stages . The advantages of early detection are not limited to cancer, and many other disorders such as Alzheimer disease are presumed to cause disruptive changes well before clinical manifestations become obvious, but profoundly nanotechnology provides an unprecedented opportunity to build better detection strategies and tools, and places the rapidly evolving field of [19, 'nanodiagnostics' at the front line in the war on diseases 30,31] . Although, pharmacogenomics focuses on the identification of genetic variants thatinfluence drug effects, typically through alterations in pharmacokinetics and new emerging analytical approaches have facilitated the evolution of a discovery model from hitherto promising drug candidates towards agnostic genome-wide analyses of patient populations with specific drug-response phenotypes highlighting "toxicity or desired pharmacological [32,33] effects .…”
Section: Toxicity Of Nanomaterialsmentioning
confidence: 99%
“…With regard to clinical science, the potential applications of nanotechnology are huge, and has already generated a range of promising examples, such as conceptually new medical diagnostics, imaging agents and therapeutics (using new drug-delivery platforms) for detecting and treating diseases [18,[26][27][28][29] in the early stages . The advantages of early detection are not limited to cancer, and many other disorders such as Alzheimer disease are presumed to cause disruptive changes well before clinical manifestations become obvious, but profoundly nanotechnology provides an unprecedented opportunity to build better detection strategies and tools, and places the rapidly evolving field of [19, 'nanodiagnostics' at the front line in the war on diseases 30,31] . Although, pharmacogenomics focuses on the identification of genetic variants thatinfluence drug effects, typically through alterations in pharmacokinetics and new emerging analytical approaches have facilitated the evolution of a discovery model from hitherto promising drug candidates towards agnostic genome-wide analyses of patient populations with specific drug-response phenotypes highlighting "toxicity or desired pharmacological [32,33] effects .…”
Section: Toxicity Of Nanomaterialsmentioning
confidence: 99%
“…Nanoplatforms allow more accurate, non-invasive and real-time cancer diagnosis and monitoring during therapy using magnetic resonance imaging, ultrasonography, etc. (Alexis et al 2008;Baetke et al 2015;Zaimy et al 2017) Adjuvant nanotechnological devices are used in cancer interventions such as radiotherapy (Wu et al 2016), photodynamic therapy (Clement et al 2017) and sonodynamic therapy (Xu et al 2016), which are capable of achieving considerably higher precision of treatment and reduced side effects. After decades of developing the understanding of nanotechnology, cancerrelated nano-treatments have undergone extensive preclinical and clinical-trial studies and shown promising results (H. .…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is one of the leading causes of death worldwide, with the number of new cases expected to rise in the next two decades. The disease is characterized by genetic abnormalities, with 125 cancer‐promoting genes having been found so far, making gene therapy a prospective way to treat cancer . Gene therapy involves the genetic modification of a patient's cells by transferring genes, gene segments, or regulatory oligonucleotides into the cells.…”
Section: Introductionmentioning
confidence: 99%